Methodological reasoning of the computer literacy standard for students - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2002)
This paper discusses the computer literacy standard of students with respect to the European Computer Driving License (ECDL) and general informatics curricula of comprehensive schools. Some aspects of relations to ECDL Start modules are analyzed. The main attention is paid to discuss the virtue attitude of using the information and communication technology as well as to general capabilities related to computer literacy. The main propositions are presented and motivated. The paper also deals with the main fields of computer literacy topics: Basic principles and concepts of applying computers (1), Basics of information processing (2), Text handling and information presentation (3), Web and electronic mail (4), Introducing spreadsheet and data base (5), Social, juridical and ethical aspects (6).